38.7k views
3 votes
6x - 8x + 5 = -2(x + 2) + 7

1 Answer

3 votes

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Hi my lil bunny!

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

~ Question :
6x-8x+5=-2(x+2)+7

________________


(Simplify.both.sides.of.the.equation.)\\6x-8x+5=-2(x+2)+7\\6x + -8x + 5 = (-2)^((x)) + (-2) (2) + 7 ( Distribute)\\6x + - 8x + 5= -2x + -4 + 7\\(6x + -8x) (5) = (-2x) + ( -4x + 7) (Combine.Like.Terms)\\-2x + 5 = -2x + 3\\( Add.2x.to.both.sides.)\\-2x + 5 + 2x = -2x + 3 + 2x\\5 = 3\\(Subtract.5.from.both.sides.)\\5 - 5 = 3 - 5\\0 = -2

Answer : There are no solutions.

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Have a great day/night!

❀*May*❀

User Manish Srivastava
by
6.8k points